2022
DOI: 10.3389/fanim.2022.1072712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary essential oil of oregano on performance parameters, gastrointestinal traits, blood lipid profile, and antioxidant capacity of laying hens during the pullet phase

Abstract: Many benefits have been found in supplementing essential oils such as oregano oil (EOO) to poultry, including increased body weight gain, antioxidant activity, and better gastrointestinal morphology. However, few studies tested the influence of EOO supplementation on laying hens and reported conflicting results regarding its efficacy in improving their health and performance. Therefore, we aimed to explore the effects of dietary EOO on performance, gastrointestinal (GIT) traits, blood lipid, and antioxidant ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Birds supplemented with oregano EO showed consistently higher concentrations of GSH-Px. Additionally, the experimental group exhibited significantly lower alanine and aspartate transferase concentrations [53].…”
Section: Antioxidant Propertiesmentioning
confidence: 88%
“…Birds supplemented with oregano EO showed consistently higher concentrations of GSH-Px. Additionally, the experimental group exhibited significantly lower alanine and aspartate transferase concentrations [53].…”
Section: Antioxidant Propertiesmentioning
confidence: 88%
“…The tolerance for the doses below 7 µL is probably due to the ability of the cells in metabolizing and detoxifying OEO compounds. In fact, many studies have shown that optimal dietary use of OEO or its main compound, carvacrol, improved different aspects of gut function and health including digestive capacity, immune status, and microbiota in chickens ( Ruan et al, 2021 ; Zhang et al, 2021 ; Gholami-Ahangaran et al, 2022 ; Johnson et al, 2022 ). In the current study, jejunal transcriptomes at hatch were compared between 2 groups, injected with either 5 μL OEO or saline, to study the compensatory mechanisms and other potential effects of nontoxic levels of OEO on the digestive and metabolic capacity of the gut during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…The increased digestibility and growth in OEO supplemented broilers were associated with elevated lipid and carbohydrate metabolism in the intestine and liver of broiler chickens ( Reyer et al, 2017 ; Bajagai et al, 2021 ). In addition, dietary supplementation of OEO resulted in improved intestinal weight and morphological measurements ( Amer et al, 2021 ; Johnson et al, 2022 ). However, not much is known about the potential effect of OEO on the embryonic development of chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Ingredient percentage and calculated nutrient analysis of the four basal diets used in the current experiment [24].…”
Section: Treatmentsmentioning
confidence: 99%